HELP WANTED–ACCOUNTANTS. - Knittel, Roger F. (The Accounting Review, 1939)
Abstract This article highlights the problems concerning accounting education in U.S. colleges. There is a feeling that college accounting courses are too ambiguous, too much of a confusion, and too theoretical. Too many college graduates feel an accounting position is theirs by right of their degree in accounting without requiring them to do any detail work. Too many people without any natural aptitude for accounting are encouraged in colleges. The first criticism, centering around class-room "theory," has been broadcast ever since the advent of the school of business administration. The second criticism is a reflection upon the type of instruction found in most schools in creating a mental attitude in the student which is not particularly beneficial. It has been found that men receive highest compensation from public accountants and metal manufacturers and the lowest salaries are paid to them by transportation companies and motion-picture exchanges. Municipalities pay the best salaries to women accountants, with public accountants second; while hospitals are the least remunerative of all.